The potential of selected agricultural waste to improve water infiltration rate in lateritic soil / Nurain Zulkifli - Zulkifli, Nurain (Faculty of Plantation and Agrotechnology, 2018)
Plantation and agricultural sector has been one of the crucial food production sources in Malaysia due to the rapid population growth. Most of the land has been utilized for residential purposes and the leftover is the marginal land such as a lateritic soil. Lateritic soil is considered as too clayey and has high bulk density which give the major problem in soil drainage. This research study was conducted to improve the water infiltration rate by using Palm Oil Mill Effluent (POME) as it is proven to reduce the bulk density due to soil aggregation by organic matter. As POME is becoming the issue on disposal, therefore this utilization will be the great alternative as it will give benefit to the soil texture. This experiment was conducted in share farm of Plantation and Agrotechnology Faculty, UiTM Jasin for 6 weeks by using Completely Randomized Design (CRD) due to homogenous texture which was silty clay loam. There were four treatments with three replications which were 2L, 4L, 6L, and 8L respectively. It is shown that the best rate was Treatment 1 (2L) as it fulfills the standard range of water infiltration rate (more than 50mm/hour) and bulk density (1.20-1.40 g/cm3) for healthy plant growth. Treatment 1 (2L) gave 68 mm/hour of water infiltration rate and 1.25 g/cm3 of bulk density with 0.570 and 0.451 of p-values respectively which is acceptable with the consideration of cost benefits, cost inputs, and profit to the industry. The not significant results might be due to types and soil textures, duration for the research to be completed, and also climate change factors.